MORPHOGENIC AND STRUCTURAL CHARACTERISTICS OF MARANDU GRASS AFFECTED BY FERTIGATION WITH TREATED SEWAGE EFFLUENT AND CUTTING HEIGHT - Dantas, Geffson de F.; Faria, Rogerio T. de [UNESP]; Costa, Nata R. [UNESP]; Santos, Gilmar O.; Ferraudo, Antonio S. [UNESP] (Soc Brasil Engenharia Agricola, 2020)
The response of biomass flow components of forage from the interaction between fertigation with wastewater and cutting height during the year is little known. The objective of this work was to verify the responses of morphogenic and structural characteristics of Urochloa brizantha as a function of fertigation application strategies with sewage treatment plant effluent (TSE), complemented with urea (U), associated with harvest with two plant heights during the dry and rainy periods. The forage cutting heights were 30 cm (H-1) and 40 cm (H-2), and nitrogen fertilization doses were 9.1(D-1), 12.1 (D-2), 22.5 (D-3), 26.6 (D-4), and 34.0 (D-5) kg of N per Mg-1 of dry matter (DM) produced, applied by TSE via fertigation, plus 7.5 kg N per Mg-1 of DM produced, applied in the form of urea by cover in all treatments. Factor analyses for the dry and rainy periods identified two processes that correspond to forage mass growth and leaf development. Analysis of variance showed that treatments D5H2 and D5H1 presented superior responses over the other treatments, in the dry, and rainy periods. The treatment D5H2 stood out in the process of forage mass growth, and D5H1 in leaf development.
Keywords: defoliation; nitrogen; water reuse